Processing of negative stimuli facilitates event-based prospective memory only under low memory load. Issue 8 (17th November 2017) - Pedale, Tiziana; Basso, Demis; Santangelo, Valerio
ABSTRACT: Event-based prospective memory (PM) is related to the ability to execute a previously planned action at the appropriate situation. Previous literature showed enhanced performance when emotional stimuli are used as PM targets. However, it was entirely unexplored whether this effect is susceptible to prospective memory load (PML), related to the number of target events that are relevant for the pending PM task. Here we presented participants with angry or neutral faces for an identity judgment (ongoing task). A different number of faces, depending on low vs. high levels of PML, served as PM targets. The results showed better PM performance following negative than neutral targets, but only under low levels of PML. This indicates that the bottom-up facilitation driven by negative stimuli serving as PM targets dramatically depends on the available attention resources allocated for monitoring the incoming information.